The insulo-opercular cortex encodes food-specific content under controlled and naturalistic conditions - Yuhao Huang; Bina W. Kakusa; Austin Feng; Sandra Gattas; Rajat S. Shivacharan; Eric B. Lee; Jonathon J. Parker; Fiene M. Kuijper; Daniel A. N. Barbosa; Corey J. Keller; Cara Bohon; Abanoub Mikhail; et al. (Nature Communications, 2021)
Animal studies have shown that insulo-opercular network function is critical in gustation and in behaviour based on anticipated food availability. The authors describe activities within the human insulo-opercular cortex which underlie anticipatory food evaluation in both controlled and naturalistic settings.